Penguatan Adaptasi Masyarakat Mengurangi Resiko Bencana Banjir di Desa Rambipuji, Kecamatan Rambipuji. - Yuninda Fitri Rahmagita; Adeliya Agustin; Dwi Nur Vita Angelasari; Rafi Akbar Santoso (Advances In Education Journal, 2026)
Flood disasters occur recurrently in Rambipuji Village, Jember Regency, due to overflow from the Dinoyo River, causing significant social and economic impacts on the community. This study aims to analyze the forms of community adaptation in reducing flood disaster risk in Dusun Tempean, Desa Rambipuji. A qualitative phenomenological approach was employed, with data collected through in-depth semi-structured interviews, structured field observations, and documentation studies. Key informants were selected using snowball sampling. The findings reveal that community adaptation occurs across three phases: before, during, and after flooding. Prior to floods, residents utilize WhatsApp groups for early warning communication, prepare emergency bags, and disconnect electrical installations. During floods, the community collaborates with Destana volunteers to operate emergency posts and conduct evacuations. Post-flood recovery involves collective mud cleaning using community-owned equipment. Analyzed through Peter L. Berger's Social Construction Theory, these adaptive behaviors have evolved from externalization into objectivation, becoming embedded social norms and shared practices that strengthen community resilience against recurring flood threats.